Terminus Positions of Jakobshavn Isbrae, Greenland, 2022-2023 ... - Picton, Hannah (NERC EDS UK Polar Data Centre, 2024)
The dataset consists of a single shapefile containing terminus positions of Jakobshavn Isbrae, Ilulissat Icefjord, Greenland, between 2022-2023. Jakobshavn Isbrae is a fast-flowing outlet glacier situated in central west Greenland and terminates in Ilulissat Icefjord, a deep fjord basin renewed by water from Disko Bay (Gladish et al., 2015). Each polyline feature in this dataset reflects a terminus position manually digitised using synthetic aperture radar (SAR) mosaics downloaded from the National Snow and Ice Data Center (NSIDC; Joughin, 2021). The dataset comprises 31 terminus positions in total, each digitised from imagery collected between 02/01/2022 and 28/12/2022. Hannah Picton acknowledges funding from the E4 DTP (Edinburgh Earth, Ecology and Environment Doctoral Training Partnership), NE/S007407/1. ... : Each terminus position was manually digitised within QGIS using Sentinel-1A and Sentinel-1B SAR mosaics (Joughin et al., 2016) downloaded from the NSIDC (Joughin, 2021). The details of each SAR mosaic from which a given terminus position was digitised is provided in the attribute table of the shapefile. ...